Perancangan Desain Karakter Pada Komik Web Sejarah Lokal “Gedangan 1904” - Yuningsih, Agustina Putri; Daniar, Aninditya; Nisa, Diana Aqidatun (Universitas Pahlawan Tuanku Tambusai, 2024)
Indonesia has a long history as a country that was colonized for almost 350 years. This makes Indonesia rich in historical heritage, both national and local in every region. The importance of building awareness of historical continuity, especially for the younger generation, is necessary to preserve historical sites and heritage. One of the efforts made is to introduce local history to the younger generation through a webcomic titled